The Effects of Doctor-Patient Consultation Applications on Treatment Adherence, Recovery Duration, and Patient Satisfaction: A Systematic Review - Susilowati, Dewi; Sriatmi, Ayun; Arso, Septo Pawelas; Kartasurya, Martha Irene (International Journal of Science and Society, 2025)
Doctor patient consultation services play a crucial role in improving healthcare delivery and patient outcomes. With the increasing adoption of telemedicine and mobile health applications, understanding the impact of these consultation services on patient adherence, recovery, and satisfaction has become essential. This study aims to evaluate the effectiveness of various consultation methods, including telemedicine and mobile apps, in enhancing treatment adherence and patient experience, particularly in managing chronic diseases such as tuberculosis and diabetes. A comprehensive literature review was conducted, analyzing empirical studies focused on doctor–patient consultations delivered through traditional, telemedicine, and mobile health platforms. Key variables examined included service quality dimensions (reliability, responsiveness, empathy), educational interventions, and the use of digital reminder systems. Studies from diverse healthcare settings and patient populations were considered to assess the influence of consultation quality and technology-assisted interventions on patient adherence and health outcomes. Findings consistently demonstrate that high-quality consultation services significantly improve patient adherence and satisfaction. Telemedicine and mobile applications contribute positively by facilitating continuous engagement and medication reminders. Educational efforts integrated into consultation processes further enhance patient knowledge and compliance. However, adherence is multifactorial, influenced by socio-economic status, health literacy, and systemic healthcare barriers. While telemedicine shows promise, challenges such as infrastructure limitations and regulatory hurdles remain. The study recommends integrating technology with empathetic, patient-centered communication and tailored educational support to optimize treatment adherence and clinical outcomes.